Expert System for Ear Disease Using the Nave Bayes Method - Pratiwi, Putri Septiani Indah; Rohman, MGhofar; Sholihin, Miftahus (Generation Journal, 2023)
An expert system is a type of artificial intelligence application that is used to tackle complex problems that require specialized knowledge. Expert systems can be used in a variety of disciplines, including healthcare, finance, and manufacturing. The aim of this study was to apply the Nave Bayes approach in a website-based ear illness diagnostic system and to determine its accuracy in an expert system for diagnosing ear disease. The naive Bayes approach is implemented in this research because it may assume that each symptom is independent of one another and can thus be used to assess the probability of a condition based on the symptoms that emerge. The results of this study show that the expert system for diagnosing ear disease using the Nave Bayes method is built on a website using the PHP programming language and the database maintained by MySQL, and this application has been tested 10 times, with 9 test data appropriate and 1 test data not appropriate. As a result of testing this application, the accuracy value obtained is 90%.